A Rare Case of Aneurysmal Bone Cyst in the Paranasal Sinus - Hashemi, Seyyed Mostafa (Iran J Otorhinolaryngol, 2015)
INTRODUCTION: Aneurysmal Bone cysts (ABC) are extremely rare in the head and neck region and even rarer in sinuses. ABC is a benign multicystic mass that is locally-destructive and rapidly expandable. Hemorrhagic fluid content (like in this case) and septated appearance are the characteristic feature of ABC. Established treatment options for ABCs include sclerotherapy, embolization, radiotherapy, simple curettage, surgical excision, or a combination of methods. CASE REPORT: In this article, a 5 year-old boy with a recurrent nasal mass is presented. The patient was finally diagnosed with this rare entity: ABC of the paranasal sinuses. The patient was treated through complete surgical removal. CONCLUSION: ABC can be considered as a rare differential diagnosis of recurrent nasal hemorrhagic mass in a pediatric population.